Climate Change, Agricultural Production, Food Security, and Livelihoods of Rural Communities in Rural Districts: A Qualitative Approach - Gusti Rusmayandi; Indriyani; Etty Sri Hertini; Muhammad Ade Kurnia Harahap; Rahmat Joko Nugroho (West Science Interdisciplinary Studies, 2023)
Climate change significantly impacts agricultural production, food security, and livelihoods of rural communities in Sukabumi District. This study examines the relationship between climate change, agricultural production, food security, and the livelihoods of rural communities in the Sukabumi District. The study used a qualitative approach, including household surveys, interviews with key informants, and focus group discussions, to gather in 20 villages. Studies have found that climate change has led to a decline in crop yields, which has led to food insecurity and decreased incomes and livelihood opportunities for rural communities. Studies have also found that rural communities have used various adaptation strategies to cope with the impacts of climate change. However, these strategies are not enough to fully address the challenges faced by rural communities. The study's findings highlight the need for effective adaptation strategies to help rural communities cope with the impacts of climate change. In addition, the study findings point to the need for more investment in climate change research and monitoring, especially at the local level, to better understand the impact of climate change on rural communities and to provide foundational information for evidence-based policymaking and decision-making. Studies have limitations, including limited sample size and reliance on self-reported data. Future research could use a longitudinal design and incorporate more objective measures of agricultural productivity and food security to understand better climate change's impact on rural communities in Sukabumi District.